N. F. S. Grundtvigs syn på forholdet mellem skabelse, åbenbaring og nærværelse belyst ved en sammenligning med Jürgen Moltmann - Præstegaard, Betina Hjorth (Grundtvig-Studier, 2002)
N. F. S. Grundtvigs syn på skabelse, åbenbaring og nærværelse belyst ved en sammenligning med Jürgen Moltmann [N. F. S. Grundtvig's views upon creation, revelation and presence in the light of a comparison with J. M. ] Af Betina Hjorth In this article N. F. S. Grundtvig is compared with the living German protestant theologian Jürgen Moltmann and Grundtvig’s continuous and actual ecumenical relevance is emphasized. Unlike most Western theologians both Grundtvig and Moltmann show an interest in the trinitarian and liturgical tradition of the Orthodox Church. Instead of the typical western focus on the revelation of Christ and the difference between revelation and history, Grundtvig and Moltmann as well as most Orthodox theologians focus on the Trinity and the nearness of God in everyday life. Because of their ontological concept of theology, which is related to Grundtvig’s and Moltmann’s desire to avoid the western distinction between Gott and sich and Gott für mich, they both stress the investigation of the relationship between the Father, Son and the Holy Spirit as the most important theological task. God is recognized as an open and integral fellowship of three divine persons - that is as love instead of as a transcendent subject. Most interesting is their analysis of the Holy Spirit whom they, in contrast to the western filolioque-tmdition, conceive as a person equal to the Father and the Son. In the first part of the article the similarities between Grundtvig and Moltmann are described by means of the old Orthodox concept of Perichoresis. Even though there are many similarities between the two theologians a more specific analysis of their literature on the Eucharist also reveals many differences between them. While Grundtvig’s theology is inspired by Luther, Moltmann shows what trinitarian and Orthodox theology looks like in a Calvinistic context. Furthermore the second part of the article describes how the inter-subjective concept of God as a fellowship causes a new social concept of theology: Theology is no longer a private reflection but a social experience - taking place in a historical (Moltmann) or liturgical and doxological (Grundtvig) context. Finally the article contains a discussion on strengths and weaknesses of the two theologians. Although the analysis shows that especially Grundtvig’s concept of the Trinity makes God living and present, both theologians offer a fruitful new understanding of theology which makes it possible to avoid the common distinction between theologia prima and theologia secunda. If one believes that Christianity is relevant in everyday life outside the university, the distinction should be avoided (though not completely eliminated).